The Analysis Of Implementation Of The Independent Curriculum In Elementary Schools - Wahyu Pertiwi, Monica; Tadzkiroh, Ummi; Sumardjoko, Bambang; Ghufton, Anik (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2023)
This research is to find out and examine the